The Fun Food Barbeque as a Product Innovation of the Food and Beverage Department, the Neo+ Awana Hotel, Yogyakarta - Carlos Iban; Arismagita Arismagita (Sekolah Vokasi, Universitas Gadjah Mada, 2017)
The growth of the hotel business in Yogyakarta is currently increasing up. Based on data from the Association of Indonesian Hotels and Restaurants, the total of new hotels to be built in Yogyakarta reaches 110 hotels. With reference to these growth figures, hospitality management is currently not only focused on providing accommodation, but also going further to selling other hotel products, such as food and beverages. This research took a case study about the product innovation of Neo + Awana Hotel Yogyakarta, with a developing event called